The Role of Buy Now Pay Later on Factors Influencing Purchase Decisions on the Shopee Application (Empirical Study of PT Deli Tools Indonesia) - Denise Insan Hirliana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
Financial innovations such as Buy Now Pay Later (BNPL) are increasingly used in e-commerce, especially by Generation Z who have a distinctive shopping character. This study aims to analyze the influence of consumer trust, impulsive buying, willingness to pay, and variety seeking behavior on purchase decisions on Shopee, with BNPL as a mediating variable. The research method used was a quantitative survey, with respondents consisting of Shopee users  aged 13-28 years. The data was obtained through a survey of Shopee Gen Z users and analyzed using  the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that impulsive buying and variety seeking behavior had a significant effect on purchase decisions, while consumer trust, willingness to pay, and BNPL did not show a significant influence. In addition, BNPL does not mediate the relationship between independent variables and purchasing decisions. In conclusion, impulsive behavior and the search for variety are the main factors driving Gen Z's purchasing decisions, while BNPL has not played a significant role in these decisions.